The Role of Islamic Religious Education Teachers in Preventing Bullying Behavior in Class XI - Nikmah, Isnatun; Aziz, Ikhwan; Hayati, Rina Mida (International Journal on Advanced Science, Education, and Religion, 2025)
The role of PAI teachers is an important factor in preventing bullying behavior at school, especially in creating a safe and comfortable learning environment. This research was aimed at finding out the role of Islamic religious education teachers in preventing bullying behavior, especially at SMK Ma'arif 1 Metro. This is due to bullying behavior at school. Therefore, the role of Islamic Religious Education teachers is very important to prevent this behavior from occurring. The method used is a qualitative method with data collection techniques obtained from the results of observations, interviews and documentation. The subject of this research is the Islamic religious education teacher in class XI TKJ SMK Ma'arif 1 Metro. The data analysis technique used is (data reduction), display data (data presentation). The results of this research are, the role of Islamic religious education teachers in preventing bullying behavior in class XI TKJ SMK Ma'arif 1 Metro